Funding Management in Improving Student Achievement at SMP PGRI 2 Ciparay - Anisa Sriwandita Yuni; R. Supyan Sauri; Ria Restu Ramadhanty; Yeni Suhaeni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
In everyday terms, the term finance or financing comes from the word finance which is associated with efforts to obtain or raise capital to finance the activities to be carried out. But lately, the meaning of finance or financing has been expanded, not only as an effort to raise capital, but also includes the dimensions of the use of capital. This broadening of understanding is the result of the awareness that capital is a scarce factor of production that needs to be utilized as well as possible. Education funding as stated in the National Education Standards: Government Regulation No. 19 of 2005 consists of 3 major parts, namely: First, investment costs include costs for providing facilities and infrastructure, developing human resources and working capital. Second, operational costs include educational costs that must be incurred by students to be able to take part in the learning process regularly and continuously. Third, personal costs.